Inhibition of Polyamine Formation Antagonizes Vascular Smooth Muscle Cell Proliferation and Preserves the Contractile Phenotype. (8th April 2014) - Grossi, Mario; Persson, Lo; Swärd, Karl; Turczyńska, Karolina M.; Forte, Amalia; Hellstrand, Per; Nilsson, Bengt‐Olof
Abstract The polyamines putrescine, spermidine and spermine play essential roles in cell proliferation and migration, two processes involved in the development of vascular disease. Thus, intervention with polyamine formation may represent a way to inhibit unwanted vascular smooth muscle cell (VSMC) proliferation. The aim of the present study was to assess the importance of polyamines for VSMC proliferation and vascular contractility. The rate‐limiting step in polyamine biosynthesis is catalysed by ornithine decarboxylase (ODC). Treatment with α‐difluoromethylornithine (DFMO), an irreversible inhibitor of ODC, reduced DNA synthesis in primary rat VSMCs in a concentration‐dependent manner with an IC50 value of 100 μM. Moreover, DFMO reduced VSMC migration assessed in a scratch assay. The DFMO‐induced attenuation of VSMC proliferation was associated with lowered cellular amount of polyamines. The antiproliferative effect of DFMO was specific because supplementation with polyamines reversed the effect of DFMO on proliferation and normalized cellular polyamine levels. Isometric force recordings in cultured rat tail artery rings showed that DFMO counteracts the decrease in contractility caused by culture with foetal bovine serum as growth stimulant. We conclude that inhibition of polyamine synthesis by DFMO may limit the first wave of cell proliferation and migration, which occurs in the acute phase after vascular injury. Besides its antiproliferative effect, DFMO may prevent loss of the smooth muscle contractile phenotype in vascular injury.